Negative Thinking and the Denial of Tolerance: The Challenge of Marcuse to Contemporary Adult Education - Stephen Brookfield (Adult Education Research Conference, 2002)
This paper seeks to insert critical theorist Herbert Marcuse’s concepts of rebellious subjectivity and repressive tolerance into adult educational discourse.